Access to Finance among Small and Medium-Sized Enterprises and Job Creation in Africa - Zuzana Brixiová; Kangoye; Thierry; Thierry Urbain Yogo (Global Labor Organization (GLO), 2020)
In the past decade inclusive growth, that is job-rich growth, has topped the policy agenda in developing countries. This paper investigates how the access to finance affects employment in small and medium-sized enterprises (SMEs) in Sub-Saharan Africa. It first presents a model where firm creation requires entrepreneurial search and paying the start-up costs, while the firm's size in terms of employment depends on the access to credit. Under the financial market imperfections, access to credit can be a binding constraint on firm entry and employment even when the banks have sufficient liquidity. Using an impact evaluation-based approach on firm-level data from 42 African countries, we show that SMEs with access to formal financing create more jobs than firms without access, with employment in firms having access to more affordable and larger loans growing the fastest. The impact of access to finance is stronger for firms in manufacturing than in services, pointing to sectoral targeting of finance as a possible policy supporting industrialization.
Keywords: L2; G2; D22; C1; 330; entrepreneurship; financial inclusion; employment; propensity score matching